Development of a supply chain risk mitigation index for distillery. Issue 3 (8th September 2020) - Raghuram, P.; Sandeep, Perumalla; Sreedharan, V. Raja; Saikouk, Tarik
Abstract : Purpose: A huge number of events can affect the operations of a long and complicated supply chain. This paper deals with the development of a supply chain risk mitigation index (SCRMI) based on a risk mitigation maturity framework. A comprehensive list of supply chain risks has been ascertained and segregated into risks faced at various supply chain echelons through a detailed literature review. Design/methodology/approach: This paper is based on an extensive literature review and questionnaire to identify risks. order of magnitude analytic hierarchy process (OM-AHP) was used as the methodology to assess the prioritization of supply chain risks under two clusters, viz., Probability and severity leading to risk were tested in a distillery. Findings: SCRMI was determined and used to categorize their maturity level in facing supply chain risks. Thus, organization can focus on improvements for their specific needs. Research limitations/implications: The model was tested in the distillery industry. It should be tested in other contexts with other methods to provide generalizability. Practical implications: This research provides direction to managers for choosing risk mitigation strategies based on the global supply chain environment. SCRMI can be a performance metric for the supply chain managers. Originality/value: The manufacturer's readiness to take action in the face of disruptions in the supply chain is a critical challenge in today's complex business environment and SCRMI framework is instrumental in such business environment.